Histopathological characterization of L. donovani infection in RAG2-/-mice (Mongolian Journal of Agricultural Sciences, 2015)
A recent study demonstrated lower incidence of fever and hepatosplenomegaly in HIV-positive VL patients than HIV-negative VL patients, indicating that acquired immunity have important roles in development of hepatosplenomegaly also in human VL. To explore the roles of acquired immunity in pathology of VL, pathological characterization of L. donovani infection in RAG2-/-mice was performed. One hundred million promastigotes were inoculated intraperitoneally to RAG2-/-mice as well as BALB/c mice, and organs were harvested from the animals at 2, 4, 8 and 12 weeks after infection and examined for parasite burdens and pathological changes. L. donovani infection induced splenomegaly in BALB/c mice; the length of the spleen after 12 weeks of infected mice was as twice as that of naive mice. In contrast, such the enlargement was not observed in RAG2-/-mice. Accumulations of mononuclear cells were found in the liver of infected BALB/c mice, whereas such the formations were less found in RAG2-/-mice. These results suggest that development of hepatosplenomegaly during experimental VL is dependent on the T cell or B cell rather than the presence of parasites.Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 43-50